Membrane topology of Golgi-localized probable S-adenosylmethionine-dependent methyltransferase in tobacco (Nicotiana tabacum) BY-2 cells. Issue 12 (2nd December 2015) - Liu, Jianping; Hayashi, Kyoko; Matsuoka, Ken
Abstract: S-adenosylmethionine (SAM)-dependent methyltransferases (MTases) transfer methyl groups to substrates. In this study, a novel putative tobacco SAM-MTase termed Golgi-localized methyl transferase 1 (GLMT1) has been characterized. GLMT1 is comprised of 611 amino acids with short N-terminal region, putative transmembrane region, and C-terminal SAM-MTase domain. Expression of monomeric red fluorescence protein (mRFP)-tagged protein in tobacco BY-2 cell indicated that GLMT1 is a Golgi-localized protein. Analysis of the membrane topology by protease digestion suggested that both C-terminal catalytic region and N-terminal region seem to be located to the cytosolic side of the Golgi apparatus. Therefore, GLMT1 might have a different function than the previously studied SAM-MTases in plants. Graphical abstract: : Protein topology of a novel S-adenosylmethionine-dependent methyltransferase on the Golgi apparatus (GLMT) in tobacco BY-2 cell.